2014
DOI: 10.1039/c4mb00083h
|View full text |Cite
|
Sign up to set email alerts
|

Can hydroxylamine be a more potent nucleophile for the reactivation of tabun-inhibited AChE than prototype oxime drugs? An answer derived from quantum chemical and steered molecular dynamics studies

Abstract: Organophosphorus nerve agents are highly toxic compounds which strongly inhibit acetylcholinesterase (AChE) in the blood and in the central nervous system (CNS). Tabun is one of the highly toxic organophosphorus (OP) compounds and is resistant to many oxime drugs formulated for the reactivation of AChE. The reactivation mechanism of tabun-conjugated AChE with various drugs has been examined with density functional theory and ab initio quantum chemical calculations. The presence of a lone-pair located on the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…The Ganguly group assessed various reactivators by QM analysis, and showed that uncharged ones are kinetically more efficient . Later, they demonstrate that the rate‐limiting step is different for charged pyridinium oximes and non‐charged pyridine oximes: both species proceed through an addition–elimination mechanism; for charged species, the rate‐determining step is elimination, whereas it is addition for uncharged species . It was also demonstrated by semi‐empirical QM/MM that the peripheral‐site moiety of the active site is helpful to bind the reactivator and to stabilize the key transition state .…”
Section: Introductionmentioning
confidence: 99%
“…The Ganguly group assessed various reactivators by QM analysis, and showed that uncharged ones are kinetically more efficient . Later, they demonstrate that the rate‐limiting step is different for charged pyridinium oximes and non‐charged pyridine oximes: both species proceed through an addition–elimination mechanism; for charged species, the rate‐determining step is elimination, whereas it is addition for uncharged species . It was also demonstrated by semi‐empirical QM/MM that the peripheral‐site moiety of the active site is helpful to bind the reactivator and to stabilize the key transition state .…”
Section: Introductionmentioning
confidence: 99%
“…The AChE's ser-OH group loses its hydrogen and, via nucleophilic reaction, forms a bond with OP. 24,25 We observed that the most reactive modification site, Y411 is a nucleophile, as shown in Figure 4b. The electro F I G U R E 1 Human albumin from PDB (1BJ5) was visualized and labeled with sites that were observed to be modified by OP or OP-like molecules using UCSF Chimera…”
Section: Op-hsa Modification Site Detectionmentioning
confidence: 72%
“…We have further carried out steered molecular dynamics (SMD) simulations to examine the role of the active site amino acid residue in stabilizing the drug molecules. It is reported that the SMD simulation technique is suitable for the study of time-dependent unbinding of the ligand molecule from the active site of the protein. The time-dependent unbinding of the inhibitor molecule from the active site of the protein in SMD simulation has been performed with the application of an external harmonic pulling force on the inhibitor molecule in the z direction, which is considered as a favorable exit route from the active site. , We have considered 2YN9 Protein Data Bank (PDB) ID for the molecular dynamics simulation with tenatoprazole and inhibitor-5 as a representative case . The maximum ligand unbinding force required for unbinding of tenatoprazole is found to be 344.2 kJ/(mol nm), while that for inhibitor-5 is 360.6 kJ/(mol nm).…”
Section: Simulationmentioning
confidence: 99%